Identifying acoustic cues for dialect profiling: Policing in multilingual communities of India - Ravina Toppo; Sweta Sinha (Indonesian Journal of Applied Linguistics, 2022)
A multilingual country such as India with numerous languages and dialects provides fertile grounds for evasive language crimes. From threat letters to ransom demands, the scope of crime is huge. The cases of illegal immigrants have only added to the fragility of international boundaries especially, during political upheavals. This leads to further vulnerability of society and also creates challenges for the police and law enforcement agencies towards timely intervention. The purpose of the study is to exhibit dialectal variation in Indian English by comparing two varieties. The current paper is based on the acoustic analysis of Indian English spoken by two distinct groups with different mother tongues. Ten native speakers of Hindi and Bangla were recorded in an anechoic chamber. A phonetically balanced passage was selected to be read. The analysis is based on Native Language Influence Detection (Perkins Grant, 2018) to derive acoustic phonetic correlates that can be used as significant identifying markers to distinguish Indian English speakers of Bangla and Hindi speech communities. The paper highlights that dialect profiling in the Indian context can be efficiently correlated with formant frequencies and Voice Onset Time for speech data. Acoustic analysis was done on PRAAT. PRAAT was used in this study because it has often been used by other similar studies to measure desired acoustic parameters simultaneously. Formant frequencies were measured at the midpoint of the vowels in the PRAAT using the LPC formant measurement algorithm. The normalization procedure was applied to the measured formant frequencies of vowels. The research affirms that acoustic analysis can provide verifiable cues for NLID. The framework can be used in the detection of native language influence in speech-centric criminal cases. The acoustic analysis shows that Indian English has subvarieties that could help in dialect profiling. The variation in Indian English vowel patterns could be due to the influence of the native language of the speakers.